Validation of Geant4 Simulation of Proton Energy Straggling: First Results - Han, Min Cheol; Grazia Pia, Maria; Saracco, Paolo (IEEE conference record - Nuclear Science Symposium & Medical Imaging Conference., 2018)
An extensive validation test is performed to assess the capability of Geant4-based simulation of proton energy straggling. This observable is relevant to many experimental scenarios, which range from medical dosimetry to nuclear and particle physics experiments. Simulations encompassing a broad variety of Geant4 physics modeling options are compared to an extended experimental data sample collected from the literature. Statistical analysis methods are used to quantify the compatibility between simulation and experiment and differences in the capability to reproduce experimental measurements associated with the physics configurations subject to test.